Novel exocrine glands in the foreleg coxae of Discothyrea ants. (November 2020) - Billen, Johan; Lin, Chung-Chi; Esteves, Flavia A.
Abstract: Workers, queens and males of all examined Discothyrea species of the ' sauteri group', that have laterally expanded frontal lobes and well-developed antennal scrobes, are characterized by two hairy areas on the outer surface of their procoxae. Histological and ultrastructural examination of Discothyrea sauteri revealed that each of these areas is associated with a novel exocrine gland: the proximal procoxal gland is formed by a cluster of 15 round secretory cells of 34 μm with numerous mitochondria, smooth endoplasmic reticulum and Golgi apparatus.Their ducts have a diameter of 0.5–1 μm.The distal procoxal gland contains 50 secretory cells of 22 μm with numerous vacuoles and lamellar inclusions, and narrow ducts with a diameter of only 0.15–0.2 μm.The differences in ultrastructural appearance and duct diameter indicate that both glands produce a different but probably pheromonal secretion. The function of these novel procoxal glands could not yet be determined, although observation of D.sauteri workers and queens shows that they make frequent and peculiar leg movements, in which the foreleg basitarsus rubs over the coxal hairy areas. The foreleg basitarsus then rubs the ipsilateral hindleg basitarsus and antenna. As a last step of the sequence, the hindleg basitarsus strokes the gaster.In addition to the occurrence of these novel procoxal glands, histological examination of D. sauteri also revealed the presence of yet another novel but smaller procoxal base gland. Ants of the ' testacea group', that have less developed frontal lobes and no antennal scrobes, do not have procoxal hairy areas, although a distinct sculpturation with small pores may occur in the corresponding areas. The related Proceratium japonicum, that has a similar lifestyle as Discothyrea, does not have any of the procoxal glands and does not display the peculiar leg movements as reported for D. sauteri . Graphical abstract: Image 1 Highlights: Discovery of 3 novel exocrine glands in the foreleg procoxa of Discothyrea ants. Unusual that class-3 glands are distinguished based on diameter of ducts. Peculiar leg movements seem to transfer secretion to gaster. Glands exist in workers, queens and males.